FAKTOR FAKTOR PENYEBAB PERGESERAN PERAN PEMANGKU ADAT DALAM PEMERINTAHAN DESA DI DESA BANJAR BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Riska Tri Purnama; Sri Erlinda; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study aims to know the role of stakeholders the custom in the village and the factors that cause a shift in the role of stakeholders the custom in the village in the village of Banjar Benai the district Benai of Kuantan Singingi. "The population in this study is the village of Banjar Benai the 3767 with 973 the head of the family are scattered in 7 villages with a sample of 97 families. The instrument collection of data and questionnaire consisting of 26 questions and interview, then the data are analyzed with descriptive of a qualitative through a percentage . from the percentage of the answers of respondents obtained answers about the role of stakeholders the custom in the village in the village of Banjar Benai the district Benai of Kuantan Singingi in the category of yes with a percentage of 75,3%, and respondents who answered did not is 24,7 %. the role of holders of the shift is in terms of divorce, the forest land, livestock, field, civil case and criminal . regarding the causes of the role of stakeholders the custom in the village in the village of Banjar Benai the district Benai of Kuantan Singingi in the category of yes with a percentage of 44% and respondents who answered did not is 56%, you know the cause of the role of stakeholders the custom in the village in the village of Banjar Benai the district Benai of Kuantan Singingi of factors: contact with other cultures, the influence of other cultures, public dissatisfaction to the field of certain areas, formal systems of education world, people are heterogeneous, the desire to move forward, increasing the population, tolerance of the action deviated (deviation), which is not an offense, the discovery of the discovery of new and open society (open stratification).Keywords: The Role Of Traditional Authorities